2021
DOI: 10.1007/s00464-021-08434-w
|View full text |Cite
|
Sign up to set email alerts
|

Technical feasibility and short-term outcomes of laparoscopic isolated caudate lobe resection: an IgoMILS (Italian Group of Minimally Invasive Liver Surgery) registry-based study

Abstract: Background Although isolated caudate lobe (CL) liver resection is not a contraindication for minimally invasive liver surgery (MILS), feasibility and safety of the procedure are still poorly investigated. To address this gap, we evaluate data on the Italian prospective maintained database on laparoscopic liver surgery (IgoMILS) and compare outcomes between MILS and open group. Methods Perioperative data of patients with malignancies, as colorectal liver me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Full texts of the remaining 15 articles were evaluated, which resulted in exclusion of another three articles which were review articles. Consequently, 12 articles [6,[10][11][12][13][14][15][16][17][18][19][20] consisting of four retrospective cohort studies [17][18][19][20] and eight case-series [6,[10][11][12][13][14][15][16] including 196 patients were considered eligible for inclusion. The study flow chart is shown in Fig.…”
Section: Search Resultsmentioning
confidence: 99%
“…Full texts of the remaining 15 articles were evaluated, which resulted in exclusion of another three articles which were review articles. Consequently, 12 articles [6,[10][11][12][13][14][15][16][17][18][19][20] consisting of four retrospective cohort studies [17][18][19][20] and eight case-series [6,[10][11][12][13][14][15][16] including 196 patients were considered eligible for inclusion. The study flow chart is shown in Fig.…”
Section: Search Resultsmentioning
confidence: 99%
“…L-CLR is a technically challenging procedure and is only performed routinely by highly experienced laparoscopic liver surgeons. 11,12,34,35 The main challenge of L-CLR is the risk for massive blood loss and the difficulty in obtaining clear resection margins. Despite these technical challenges, L-CLR when performed safely has been shown to offer all the advantages of LLR 36 such as decreased surgical blood loss and length of stay.…”
Section: Discussionmentioning
confidence: 99%
“…Unsurprisingly, most resections for caudate lobe lesions are still performed via the open approach. L‐CLR is a technically challenging procedure and is only performed routinely by highly experienced laparoscopic liver surgeons 11,12,34,35 . The main challenge of L‐CLR is the risk for massive blood loss and the difficulty in obtaining clear resection margins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations